Healthy Living: High Blood Pressure - Linda B. Bobroff; Leigh Ann Martin (EDIS)
High blood pressure is increased pressure of blood inside the blood vessels. Too much pressure causes more work for the heart. Another name for high blood pressure is hypertension. About one in three American adults has hypertension and about half of them do not know they have this health problem. This 2-page fact sheet was written by Linda B. Bobroff and Leigh Ann Martin and published by the UF Department of Family Youth and Community Sciences, September 2013.